Capacity of Graduates through the Employer's Assessment - Lan, Le Chi (VNU Journal of Science: Education Research; Vol 37 No 1DO - 10.25073/2588-1159/vnuer.4466, 2021)
This paper studies the employer’s assessment of graduates’ capacity in 3 aspects: knowledge, skills and personal qualities. The paper surveys 200 users of graduates majoring in economics. Based on the analysis of the survey results, the paper draws conclusions about the gradaduates’ level of responsiveness to the employer’s requirements. This helps training institutions improve their training programs to meet the changing needs of society.